GERAKAN PEMBARUAN TASAWUF DI INDONESIA - Al-Kumayi, Sulaiman (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2013)
Abstract: This article aims to elaborate on Sufism reform movement in Indonesia. There former of Islam in Indonesia realize that Sufism is an integral part of Islam, therefore they are not hostile to Sufism, but tends to purify the Sufism of deviant practices. Irregularities which they saw in the midst of the Muslim community but claimed as part of Sufism must be cleaned. Sufism must be free of elements of heresy or shirk that could tarnish the purity of Islam. In this article, the author presents the figure of Hamka as a representation of Sufism reform movement in Indonesia. Although Hamka very appreciative, even followers of Sufism, he was never affiliated to the sufi order schools anywhere in the world.He also never made a separate congregation flow, as was common in the realm of the sufi order. Abstrak: Artikel ini bertujuan untuk mengelaborasi gerakan pembaruan tasawuf di Indonesia. Para pembaru Islam di Indonesia menyadari bahwa tasawuf merupakan bagian integral dalam Islam, karena itu mereka tidak memusuhi tasawuf, tetapi cenderung untuk memurnikan tasawuf dari praktik-praktik yang menyimpang. Penyimpangan yang mereka lihat di tengah-tengah masyarakat Muslim tetapi diklaim sebagai bagian dari ajaran tasawuf haruslah dibersihkan. Tasawuf harus terbebas dari unsur-unsur bid’ah atau syirik yang dapat menodai kemurnian ajaran Islam. Dalam artikel ini, penulis menyajikan sosok Hamka sebagai representasi dari gerakan pembaruan tasawuf di Indonesia. Sekalipun Hamka sangat apresiatif, bahkan pengamal tasawuf, ia tidak pernah berafiliasi ke aliran tarekat mana pun di dunia ini. Ia juga tidak pernah membuat aliran tarekat tersendiri, sebagaimana lazimnya dalam dunia tarekat. Keywords: neo-sufisme, bid’ah, al-Quran, al-Sunnah, tarekat.